Не проходите мимо любви - Асадов Эдуард Аркадьевич (Эксмо-Пресс, 2000)
Экземпляры: Ермолаевская с/б (20240212) / Инвентарный номер: 47984 / Цена: / Авт.знак: А 90 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-5